Lysine acetylation contributes to development, aflatoxin biosynthesis and pathogenicity in Aspergillus flavus. (25th October 2019) - Yang, Guang; Yue, Yuewei; Ren, Silin; Yang, Mingkun; Zhang, Yi; Cao, Xiaohong; Wang, Yinchun; Zhang, Jia; Ge, Feng; Wang, Shihua
Summary: Aspergillus flavus is a pathogenic fungus that produces carcinogenic aflatoxins, posing a great threat to crops, animals and humans. Lysine acetylation is one of the most important reversible post‐translational modifications and plays a vital regulatory role in various cellular processes. However, current information on the extent and function of lysine acetylation and aflatoxin biosynthesis in A. flavus is limited. Here, a global acetylome analysis of A. flavus was performed by peptide pre‐fractionation, pan‐acetylation antibody enrichment and liquid chromatography–mass spectrometry. A total of 1313 high‐confidence acetylation sites in 727 acetylated proteins were identified in A. flavus . These acetylation proteins are widely involved in glycolysis/gluconeogenesis, pentose phosphate pathway, citric acid cycle and aflatoxin biosynthesis. AflO ( O ‐methyltransferase), a key enzyme in aflatoxin biosynthesis, was found to be acetylated at K241 and K384. Deletion of aflO not only impaired conidial and sclerotial developments, but also dramatically suppressed aflatoxin production and pathogenicity of A. flavus . Further site‐specific mutations showed that lysine acetylation of AflO could also result in defects in development, aflatoxin production and pathogenicity, suggesting that acetylation plays a vital role in the regulation of the enzymatic activity of AflO in A. flavus . Our findings provide evidence for the involvement of lysine acetylation in various biological processes in A. flavus and facilitating in the elucidation of metabolic networks.